1997
DOI: 10.1046/j.1365-2362.1997.2210762.x
|View full text |Cite
|
Sign up to set email alerts
|

The diaphragm in chronic obstructive pulmonary disease: how useful is it?

Abstract: The respiratory muscle pump should be considered an essential organ, and the diaphragm is normally the most important inspiratory muscle in man [1], accounting for approximately 70% of resting ventilation. Diaphragm dysfunction would reasonably be expected to impose limits on ventilatory performance and, in the extreme case of neuromuscular disease, this is easily demonstrated [2,3]. Probably the most common potential cause of diaphragm dysfunction in clinical medicine is that associated with chronic obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Currently, first world countries are experiencing an increase in populations over the age of 60 as never seen before Approximately 16% of the US population is over the age of 65 [42], while 22% is over the age of 60 in the United Kingdom [43]; 24% of German citizens are age 60 or older [44] Notably, Germany experienced their largest number of centenarians in 2020 at over 20 000 individuals [44], emphasizing the growing importance of understanding the biological complexities of ageing Additionally, respiratory diseases are a leading cause of death worldwide whether chronic such as chronic obstructive pulmonary disorder (COPD) or acute such as a lower respiratory infection [45,46] Age-related changes of the lung encompass reduction in thoracic cavity size and respiratory force [47] as well as changes which disrupt cellular and molecular homeostasis [48], culminating in an increased risk of respiratory failure for individuals over the age of 60 [49] As we age, there is an exponential atrophy of skeletal muscle function surrounding the thoracic cavity [50,51] reducing its total volume capacity and reducing inspiratory and expiratory strength [52] The strength of the thoracic diaphragm, the dominant muscle involved in respiration, is significantly reduced in adults 67 and over [53] Pathogen clearance and response is significantly reduced as we age The first line of defense within the upper and lower airways is mucociliary clearance which also becomes impaired with age [54,55] This is particularly impactful when considering that expiratory strength is required for adequate clearance of particulates that cannot be cleared through mucociliary action [56,57] These structural changes demonstrate a reduced ability for elderly individuals to meet respiratory needs should pulmonary stress occur (Fig. 1) In normal ageinglungs, transcriptomic studies have revealed permanent re-modeling of the extracellular matrix Parenchymal tissue composition in mice 24 months old (aged), as opposed to 8 week-old mice (young), exhibit increased expression of the pro-fibrotic cytokines IL-1b, IL-6, and TNF-a [58 ] It is well established that lung fibrosis can impair normal lung function [59], and ageing promotes lung fibrosis Patients with sarcoidosis experience an upregulation in these same pro-fibrotic cytokines [60].…”
Section: Ageing and Comorbid Conditionsmentioning
confidence: 99%
“…Currently, first world countries are experiencing an increase in populations over the age of 60 as never seen before Approximately 16% of the US population is over the age of 65 [42], while 22% is over the age of 60 in the United Kingdom [43]; 24% of German citizens are age 60 or older [44] Notably, Germany experienced their largest number of centenarians in 2020 at over 20 000 individuals [44], emphasizing the growing importance of understanding the biological complexities of ageing Additionally, respiratory diseases are a leading cause of death worldwide whether chronic such as chronic obstructive pulmonary disorder (COPD) or acute such as a lower respiratory infection [45,46] Age-related changes of the lung encompass reduction in thoracic cavity size and respiratory force [47] as well as changes which disrupt cellular and molecular homeostasis [48], culminating in an increased risk of respiratory failure for individuals over the age of 60 [49] As we age, there is an exponential atrophy of skeletal muscle function surrounding the thoracic cavity [50,51] reducing its total volume capacity and reducing inspiratory and expiratory strength [52] The strength of the thoracic diaphragm, the dominant muscle involved in respiration, is significantly reduced in adults 67 and over [53] Pathogen clearance and response is significantly reduced as we age The first line of defense within the upper and lower airways is mucociliary clearance which also becomes impaired with age [54,55] This is particularly impactful when considering that expiratory strength is required for adequate clearance of particulates that cannot be cleared through mucociliary action [56,57] These structural changes demonstrate a reduced ability for elderly individuals to meet respiratory needs should pulmonary stress occur (Fig. 1) In normal ageinglungs, transcriptomic studies have revealed permanent re-modeling of the extracellular matrix Parenchymal tissue composition in mice 24 months old (aged), as opposed to 8 week-old mice (young), exhibit increased expression of the pro-fibrotic cytokines IL-1b, IL-6, and TNF-a [58 ] It is well established that lung fibrosis can impair normal lung function [59], and ageing promotes lung fibrosis Patients with sarcoidosis experience an upregulation in these same pro-fibrotic cytokines [60].…”
Section: Ageing and Comorbid Conditionsmentioning
confidence: 99%
“…Among other potential factors, such as chronic muscle tissue underperfusion and hypoxia, it is likely that physical inactivity and muscle disuse contribute significantly to these abnormities in skeletal muscle function (Rehn, Munkvik, Lunde, Sjaastad, & Sejersted, ; Serres et al., ). Indeed, this forms the concept of a ‘dyspnoea spiral’ (Cooper, ; Polkey & Moxham, ; Ramon et al., ), whereby patients avoid physical exertion to prevent the manifestation of dyspnoea, which consequently leads to further skeletal muscle deconditioning and metabolic derangements. In this way, dyspnoea and exercise intolerance can spiral downwards over time (Figure ).…”
Section: Skeletal Muscle Afferent Feedback and Ventilatory Control In Chronic Disease Statesmentioning
confidence: 99%
“…(), where reduced respiratory capacity, increased mechanical loading and/or ventilatory demand results in an enhanced neural respiratory drive required for ventilation, and ultimately, increased intensity of breathlessness. This model has been integrated with the concept of a dyspnoea spiral (in green; Cooper, ; Polkey & Moxham, ), whereby breathlessness leads to a spiral of physical inactivity, skeletal muscle deconditioning/dysfunction and further breathlessness. The red components illustrate the potential effect of enhanced/sensitized skeletal muscle afferent feedback as a ‘neural link’ between skeletal muscle dysfunction and breathlessness/exercise intolerance…”
Section: Skeletal Muscle Afferent Feedback and Ventilatory Control In Chronic Disease Statesmentioning
confidence: 99%